Christian Teachings on Marriage and Its Impact on Customary Marriage among the Iteso of North Teso - Maua , Anna C.; Ayanga , Hazel; Kahiga , Joseph (African Journal of Education,Science and Technology (AJEST), 2020)
The Iteso are the sub group of Plain Nilotes found in Western Kenya. The Iteso as community observe their traditional practices and rites on marriage. Christianity brought different teachings on marriage. Despite these new teachings, the Iteso continued to preserve their traditional practices in relation to marriage. The study focuses on the Iteso marriage rites and practices, and the extent to which Christianity and other variables such as modernisation, urbanisation and westernisation have influenced those rites and practices among the Iteso of North Teso sub-County. The purpose of this study was to investigate the Christian impact on the Iteso marriage rites and practices. The objectives of the research were: to examine the Christian teachings on marriage and how they have been adopted by the Iteso of North Teso.To investigate how Christianity has caused an impact on Iteso customary marriage. Questionnaires and focus group discussions were used to interview the respondents in North Teso. Purposive sampling, and snowballing were also used in order to reach the selected respondents. Functionalist theory of attitudes by Katz and Snarnoff was used. This theory states that attitudes are determined by the functions they serve for us. People hold given attitudes because these attitudes help them achieve their basic goals. The four major functions of attitudes include: adjustment functions, ego defensive function, value expressive function; and knowledge function. The Roman Catholic and the Anglican churches were sampled because they are the dominant denominations in the study area; a total of twenty four respondents were interviewed to get in-depth information. The above methods were enriched by information sought from published and unpublished literature in Kenya. Data was classified and coded into similar themes and descriptive analysis applied to get the findings. The findings indicate that: while Christianity emphasise on monogamy as the legal form of marriage, the Iteso on the other hand view the three forms like wife-inheritance, polygamy and monogamy as legal: the Iteso still value some of their traditions on marriage in spite of Christian influence and other variables such as westernization, modernization, urbanization, among others:. The study recommends that scholars can research on birth, naming and death rites, among other communities or the concept of polygamy and the church in Kenya.